Bridging Faith and Tradition: A Discourse on Moderate Islamic Path in Jambi Malay Seloko - Adeni Adeni; Osman Koroglu; Rafi’ud Derajat (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2023)
Islam-based local wisdom is unique because it represents a moderate religious path. This article analyzes how the moderate path works in the Jambi Malay traditional seloko. The Jambi Malay people have customs that guide their lives. By using a qualitative method based on content analysis, where data was collected by (1) reading Jambi Malay traditional seloko documents and (2) interviews with Jambi Malay traditional leaders, this study proves that Jambi Malay traditional seloko displays a harmonious dialogue between Islam and the locality. In the case of the seloko adat regarding washing the village (cuci kampung), for example, as a punishment for committing adultery, the discipline of stoning (rajm) or flogging (jild) as per Islamic law is not applied, even though it is said that the Jambi custom is a custom that originates from Islamic Law. In this case, the people of Jambi use a substitute punishment for stoning and flogging, which is marrying the two adulterers. The Islamic law based on the Qur’an and hadith textually is not applied as the Indonesian state is not based on sharia. It is a form of dialogue between Islam and Jambi local wisdom according to the concept of the moderate Islamic path. Apart from that, there are several other values, such as tolerance, democracy, and nationality. The findings of this study can strengthen the study of Islamic moderation in the context of local wisdom amidst various damaging accusations against local Islam as impure Islam.